A Comprehensive Review on Solid LIPID Nanocarriers for Enhanced Bioavailability of Poorly Soluble Anticancer Drugs (Asian Journal of Pharmaceutics (AJP), 2025)
Acalabrutinib and sunitinib, potent anticancer agents, face significant challenges in clinical use due to their poorsolubility, limited bioavailability, and off-target toxicity. Solid lipid nanocarriers (SLNs) have emerged as aversatile drug delivery platform capable of addressing these limitations. SLNs offer advantages such as improvedsolubility, protection against enzymatic degradation, controlled drug release, and targeted delivery, making themideal for enhancing the therapeutic potential of these drugs. This review explores the formulation strategies,mechanisms of bioavailability enhancement, and recent advancements in SLN technology for the delivery ofacalabrutinib and sunitinib. Key topics include the role of SLNs in improving drug absorption, overcoming firstpassmetabolism, and achieving tumor-specific targeting. Emerging trends such as functionalized SLNs, hybridnanocarriers, and stimuli-responsive systems are highlighted, showcasing their potential for precision oncology.While SLNs demonstrate promising results in preclinical studies, challenges such as scalability, long-term stability,and regulatory hurdles must be addressed for successful clinical translation. This review provides a comprehensiveoverview of SLNs as a transformative approach for enhancing the bioavailability of acalabrutinib and sunitinib,emphasizing their potential to revolutionize cancer therapy through innovative drug delivery solutions.